UTILIZATION OF SENTINEL-2A IMAGERY FOR MAPPING THE DISTRIBUTION OF MANGROVE FORESTS IN THE MANDEH AREA, WEST SUMATERA PROVINCE - Shahna Qintania Meron; Triyatno Triyatno (International Remote Sensing Applied Journal, 2022)
Mangroves are a part of the coastal ecosystem, mangroves play an important role in coastal ecosystems where the presence of mangroves can prevent abrasion. This study aims to identify the distribution of mangroves in the Mandeh Area using Sentinel 2A Imagery data assisted by geospatial technology tools. The methods used in this research are Normalized Difference Vegetation Index (NDVI), overlay, and maximum likelihood guided classification, these three methods are a combination of techniques from remote sensing and geographic information systems. The results of the study show that in 2015 the total area of ​​mangrove land was 437 ha, in 2020 the area of ​​mangrove forest with the most extensive mangrove forest density was a high density of (227 ha/ 68%).